Proteomic analysis revealed the biofilm-degradation abilities of the bacteriophage UPMK_1 and UPMK_2 against Methicillin-resistant Staphylococcus aureus - Dakheel, Khulood Hamid; Abdul Rahim, Raha; Al-Obaidi, Jameel R; Kumari Neela, Vasantha; Tan, Geok Hun; Mat Isa, Mohd Noor; Razali, Nurhanani; Yusoff, Khatijah (Springer, 2022)
Objective: The degradation activity of two bacteriophages UPMK_1 and UPMK_2 against methicillin-resistant Staphylococcus aureus phages were examined using gel zymography. Methods: The analysis was done using BLASTP to detect peptides catalytic domains. Many peptides that are related to several phage proteins were revealed. Results: UPMK_1 and UPMK_2 custom sequence database were used for peptide identification. The biofilm-degrading proteins in the bacteriophage UPMK_2 revealed the same lytic activity towards polysaccharide intercellular adhesin-dependent and independent of Methicillin-resistant Staphylococcus aureus (MRSA) biofilm producers in comparison to UPMK_1, which had lytic activity restricted solely to its host. Conclusion: Both bacteriophage enzymes were involved in MRSA biofilm degradation during phage infection and they have promising enzybiotics properties against MRSA biofilm formation.